Effectiveness of pulse oximetry screening for congenital heart disease in asymptomatic new-borns - Lanker, Audil Mohmad; Chowdhary, Javed; Jeelani, Nasir; Jeelani, Shazia; Hassan, Ashfaq Ul; Wani, Nasir-ud-din (International Journal of Research in Medical Sciences, 2017)
Background:Congenital Cardio-Vascular Malformations (CCVMs) are relatively common with a prevalence of 5-10 in every 1000 live births. CCVM represents a new-born condition that would be ideally suited to a screening program if simple and reliable methods were available. Pulse oximetry has been proposed as a screening method for the detection of congenital heart defects. Methods:Hospital based prospective non-randomized study conducted over a period of one year at the department of pediatrics in G.B. Panth hospital (Neonatology) and L.D. hospital (Neonatology). A total of 1200 asymptomatic new-borns attending G.B. Panth, neonatology/L.D. neonatology were screened with pulse oximetry. Oximetric screening for CCVM was performed by obtaining a single determination of postductal saturation at >24 hours. All new-borns underwent additional evaluation by echocardiography. Results:Out of 1200 newborns screened three had postductal saturation ≤95%. Echocardiography revealed TGA (transposition of great vessels) in one; TA (truncus arteriosus) in other and third one had structurally normal heart on echocardiography. There was one false negative screen (found in the inpatient records of G.B. Panth hospital). The sensitivity, specificity, positive predictive value and negative predictive value of pulse oximetry in screening for CCVM in asymptomatic new-borns was found to be 66.67%, 99.9%, 66.67% and 99.9% respectively. Conclusion:This screening test is simple, non-invasive and inexpensive. The sensitivity, specificity, and predictive value in this population were satisfactory, indicating that screening should be applied to larger populations, particularly in developing countries where lower rates of detection result in increased CCVM prevalence in asymptomatic new-borns.